Quantification of Interactions between Sand and Pyrolyzing Biomass Particles in Fluidized-Bed under Fast Pyrolysis Conditions Pertinent to Bio-Oil Production - Burton, A.; Wu, Hongwei (American Chemical Society, 2015)
This paper deals with quantification of the interactions between the sand particles and the pyrolyzing biomass particles that are thermally thin (Biot Number < 0.1) to form bed agglomerates in a fluidized-bed reactor during fast biomass pyrolysis at 500 °C, which is pertinent to bio-oil production. A new parameter, i.e., sand loading (SL) is introduced, which is defined as the mass of sand sticking to the pyrolyzing biomass particles in the bed to form bed agglomerates normalized to the total mass of biomass fed into the fluidized-bed reactor. The values of SL can be estimated experimentally. It was found that SL is a powerful diagnostic parameter for investigation into the interactions between the pyrolyzing biomass particles and the sand particles in the fluidized bed. During continuous feeding of the biomass into the reactor, the sand in the bed and the pyrolyzing biomass particles interact in a negative order reaction kinetic of 0.4. During holding upon the completion of biomass feeding, the sand and biomass particles interacted in a zero-order mechanism with respect to holding time, suggesting that the sand particles attach to the “active sites” (as part of the sticky agents) produced from biomass fast pyrolysis for forming bed agglomerates. It was also found that during continuous feeding, SL decreases from 2.4 to 0.8 g_sand/g_biomass_feed (db). At a low feed fraction (<12% of the bed mass), the formed bed agglomerates are mainly sand-char bonded but at higher feed fractions the char-char bonding becomes more important.